Treatment of material surfaces with bacterial solutions to initiate the deposition of calcium carbonate. Review - L. V. Ilyina; L. N. Tatski; K. S. Dyakova (Вестник СибАДИ)
Introduction. Surface treatment plays an important role in protecting decorative stone and concrete from the effects of harmful environmental factors. To protect stone surfaces, dietary supplements in the form of carbonatogenic bacteria, the product of which is calcium carbonate, can be used.Materials and methods. The selection and analysis of publications containing the results of research and experiments, which allow to draw conclusions about the feasibility of using bacterial solutions for surface treatment, has been carried out.Conclusions. The formation of a layer of calcium carbonate on the surface of the material reduces gas permeability, reduces water absorption, increasing the durability of concrete. It was found that the surface treatment of cement stone with solutions containing cultures of urobacteria strengthens the surface layer of the stone, but does not restore its strength. It is important that the formed layer of calcium carbonate on the surface of the material does not clog its pores. The chemical and structural similarity between the processed material and the resulting carbonate compounds must be observed. The dosage of urea and calcium chloride should correspond to the number of bacterial cells, since excess components of the nutrient medium leads to their accumulation in the pores.